Assistive Artificial Intelligence as a Cognitive Right: A proposal for neurodivergent equity in the 21st century (Research, Society and Development, 2025)
This article proposes the recognition of Assistive Artificial Intelligence (AAI) as a fundamental cognitive right for neurodivergent people. We argue that responsive AI systems operate as Cognitive Navigation Interfaces, reducing executive overload, filtering informational noise, increasing environmental predictability, and making institutional complexity more accessible. We introduce the concept of the Assistive Cognitive Ecosystem (ACE), a configuration in which one or multiple AI systems operate in parallel to support internal organization, emotional regulation, institutional communication, and decision-making. We also propose the creation of the Assistive Digital Architecture (ADA), a national protocol for the certification, ethical standardization, and integration of AAI into Brazil’s Digital SUS. AAI is presented as an emerging pillar of cognitive democracy capable of reducing structural inequality and expanding the autonomy of neurodivergent populations.